Pelatihan Penguatan Kapasitas Masyarakat Menuju Desa Tangguh Bencana Di Desa Rembitan - Ibrahim, Ibrahim; Pratama, Inka Nusamuda; Zitri, Ilham (STMIK Royal, 2024)
The main problem in partner locations is the lack of community awareness in responding to disasters; residents do not yet understand the risks and impacts of natural disasters and preventive measures that can be taken to reduce losses. This lack of knowledge makes the community unprepared and slow to respond to emergencies, ultimately increasing their safety and well-being risk. The training includes counselling sessions, workshops, and disaster simulations. Each session is designed to provide an in-depth understanding of the types of disasters, mitigation techniques, evacuation, and first aid steps. The results of this training showed a significant increase in the preparedness and response of the Rembitan Village community to emergencies. The post-disaster simulation evaluation also showed an increase in the participants' practical abilities in dealing with disasters. This program strengthens social structures and solidarity between residents and creates a model that can be applied in other villages with similar disaster risks. With ongoing support, Rembitan Village is expected to become a successful example of building community resilience to disasters, ultimately improving its residents' welfare and security. Keywords: capacity; strengthening; mitigation; disaster resilient Abstrak: Masalah utama yang terjadi ditempat mitra yaitu kurangnya kesadaran masyarakat dalam menyikapi bencana, selain itu warga belum memahami risiko dan dampak dari bencana alam, dan langkah-langkah pencegahan yang dapat diambil untuk mengurangi kerugian. Kurangnya pengetahuan ini membuat masyarakat tidak siap dan lambat dalam merespons situasi darurat, yang pada akhirnya meningkatkan risiko terhadap keselamatan dan kesejahteraan mereka. Pelatihan mencakup sesi penyuluhan, workshop, dan simulasi bencana. Setiap sesi dirancang untuk memberikan pemahaman mendalam mengenai jenis-jenis bencana, teknik mitigasi, serta langkah-langkah evakuasi dan pertolongan pertama. Hasil dari pelatihan ini menunjukkan peningkatan signifikan dan respons masyarakat Desa Rembitan terhadap situasi darurat. Kegiatan pelatihan di Desa Rembitan menunjukkan peningkatan kesadaran dan kesiapsiagaan masyarakat dalam menghadapi bencana. Masyarakat kini lebih memahami risiko bencana dan langkah mitigasi yang perlu diambil, Selain itu, mereka telah mempraktikkan simulasi bencana yang meningkatkan kemampuan mereka merespons situasi darurat. Kata kunci: kapasitas; penguatan; mitigasi; tangguh bencana